Analisis Data Mikrotremor Untuk Mengetahui Nilai Indeks Kerentanan Seismik Di Kecamatan Jambi Luar Kota - Airunisa, Airunisa; Resta, Ichy Lucya; Ngatijo, Ngatijo (Himpunan Ahli Geofisika Indonesia (HAGI), 2024)
Jambi Luar Kota Subdistrict is located in a regional geology which is dominated by sedimentary layers and has the highest population density in Muaro Jambi Regency. The population that continues to increase has resulted in regional development in the form of infrastructure development, shops, roads, housing and high-rise buildings increasing very rapidly. In this development planning, information is needed regarding land conditions and regional stability conditions against the threat of soil movement by identifying the dynamic characteristics of the soil layer which includes the value of the seismic vulnerability index (Kg). The value of Kg was obtained by calculating the values ​​of fo and Ao from the results of microtremor data processing as many as 61 measurement points using the HVSR method. The fo values ​​obtained ranged from 0.31 to 6.08 Hz and the Ao values ​​ranged from 0.99 to 2.89. The Kg values ​​obtained ranged from 0.16 to 16.62 with a relatively high distribution of Kg values ​​in Sembubuk Village, Rengas Bandung, Kedemangan, Sarang Burung, Senaung, Penyengat Olak, Sungai Duren, Muaro Pijoan, Mendalo Darat, Mendalo Indah, Mendalo Laut, Muaro Pijoan, and Pematang Jering which show these areas are more susceptible to damage if there is ground movement. Key words : Microtremor, dominant frequency, amplification, seismic susceptibility index,HVSR